Influence of acoustic feedback on boat speed and crew synchronization in elite junior rowing - Schaffert, N.; Mattes, K. (International Journal of Sports Science & Coaching, 2016)
Coordination and crew synchronization are essential for a smooth boat run in rowing. The aim of this study was to investigate the effects of acoustic feedback on boat speed, rowing technique, and crew synchronization in elite junior rowing. Thirty junior athletes (A, B-squad) participated in the field study in two measuring series in a total of eight boats. Measuring included handle forces, rowing angle, boat acceleration, and distance traveled at two training intensities (20, 22 strokes/minute). Also, blood lactate and heart rate were collected. Boat acceleration-time traces were sonified into online acoustic feedback and presented via speakers during rowing. A repeated measures within-participant factorial analysis of variance compared sections with and without acoustic feedback (a=0.05). Significantly faster boat speed with acoustic feedback compared to baseline was found for both squad levels. The time structure of rowing cycles was improved (prolonged duration of positive acceleration). No differences were found for handle power and physiological data. Parameters of crew synchronization showed reduced ranges for the time during drive and recovery phase, rhythm quotient, and handle speed during the drive phase with acoustic feedback compared to baseline. Questioning of athletes showed the benefits of acoustic feedback as supportive for technique training in elite junior rowing. ABSTRACT FROM AUTHOR